Convictions on Themselves and on the World of Minors Staying in Correctional Facilities - Irena Mudrecka (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The aim of the conducted research was to identify adaptive and maladaptive beliefs facilitating or hindering the functioning of youth in social life. The research was conducted among 146 wards of resocialization centers and 134 junior high and high school students (comparative group). The focus was on presenting some of the research results obtained using the Positive Orientation Scale (in the Polish adaptation of Mariola Łaguna, Piotr Oleś and Dorota Filipiuk) and the Scale Zero-Sum Game Belief (by Joanna Różycka and Bogdan Wojciszke). Positive orientation is the personality dimension that determines the individual's willingness to receive and process information about themselves and the world with a positive attitude, as well as highlighting the positive aspects of life. In turn, the belief that life is a zero-sum game is related to the conviction about the antagonistic nature of human relations resulting from the belief that the world's goods are limited and that therefore the success of one man is inseparable from the defeat of the other. For those who believe that life is a zero-sum game, the world is an arena of constant struggle with others who cannot be trusted to pursue their own interests. The results obtained confirm the negative correlation between the variables studied. The observed relationship between positive orientation and zero-sum game belief facilitates understanding of the views of adolescents who are in conflict with the law and customs, which, according to the cognitive concept, have an impact on their decisions and the quality of interpersonal relationships.